FTIR and NMR studies on lignin acetylation - Cateto, C.A. (2011)
In this work, a comparative study of an acetylation procedure, using four different lignin samples was performed. The chosen lignin samples, Indulin AT (Meadwestvaco), Alcell (Repap), Curan 27-11P (Borregaard LignoTech) and Sarkanda (Granit SA), represent both the guaiacyl and guaiacyl-syringyl type, and were obtained from different pulp processes (kraft and organosolv). Lignin was acetylated using an acetic anhydride-pyridine mixture and the final sample was recovered by precipitation. Final samples, with different reaction times (1 and 2 hours), were characterized by FTIR and 13C NMR analysis, and the obtained spectra were compared with the corresponding ones for non-acetylated samples. Within the used experimental conditions and samples, an incomplete acetylation yield appeared to be common. Total hydroxyl content, determined independently by titration and based on the 13C NMR results, was found to be in close agreement.